(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2011)
Idiopathic intracranial hypertension (IIH) is the persistent increase in intracranial pressure in the absence of any intracranial lesions. Though termed idiopathic IIH is known to be associated with a wide variety of disease conditions and drugs i.e. SLE, adrenal insufficiency, Cushing disease, hypoparathyroidism, hypothyroidism, iron deficiency, vitamin A, tetracycline, nalidixic acid, steroid withdrawal and many others. IIH is a rare disease, but IIH developing after replacement of levothyroxine is even rarer. Only a handful of cases of IIH associated with levothyroxine therapy have been mentioned in the literature. We are reporting a case of IIH developing after starting levothyroxine replacement and then the literature is reviewed. DOI: 10.3329/jbsp.v29i1.7173 J Bangladesh Coll Phys Surg 2011; 29:49-51